Investigating the Impact of Ethnic Tourism on Sustainable Tourism in Terms of Tourism Development in Tabriz City - Ali Zeynali Azim; MirSaid Moosavi; Farzad Zarbakhsh; Ayda Mostafazadeh Bazargan (اکولوژی انسانی, 2025)
Ethnic tourism, as a significant branch of cultural tourism, has notable impacts on various dimensions of sustainable development, particularly in the social-cultural, physical, economic, and environmental aspects. The main objective of this study is to examine the role of ethnic tourism in the sustainable development of Tabriz city. This research is descriptive-analytical and applied in nature, with data collected through a researcher-designed questionnaire. The target population includes both domestic and international tourists, as well as residents of Tabriz who have visited the city at least once or live there. The sample size, determined using Cochran's formula with an unlimited population and a 95% confidence level, is 384 individuals. The sampling method is random, involving both tourists and residents of the city. For data analysis, Structural Equation Modeling (SEM), correlation, regression, and path analysis methods were employed, and the data were analyzed using Smart PLS and SPSS software. The results of the study indicated that ethnic tourism has positive and significant impacts on various aspects of sustainable development in Tabriz. In the socio-cultural dimension, local customs and handicrafts, with a path coefficient of 0.48, have a positive impact on strengthening cultural identity and social relationships. In the physical dimension, staying in local homes, with a path coefficient of 0.43, contributes to preserving urban spaces and strengthening connections with indigenous architecture. In the economic dimension, local handicrafts, with a path coefficient of 0.50, and the participation of local communities, with a path coefficient of 0.45, play a crucial role in creating sustainable employment and distributing economic benefits among local people. This study shows that ethnic tourism can be a significant factor in the sustainable development of Tabriz and, if managed properly, can improve the economic situation, preserve cultural-social identity, and protect the natural and built heritage of the city.